A multiplex PCR assay for the detection of five human pathogenic Vibrio species and Plesiomonas. (February 2021) - Guan, Hongxia; Xue, Panpan; Zhou, Haijian; Sha, Dan; Wang, Duochun; Gao, He; Li, Jie; Diao, Baowei; Zhao, Hongqun; Kan, Biao; Zhang, Jingyun
Abstract: A multiplex PCR (mPCR) assay was established to detect five pathogenic Vibrio species and Plesiomonas shigelloides . Twelve genes were included: ompW, ctxA, rfbN, and wbfR from V. cholerae ; tl, tdh, and trh from V. parahaemolyticus ; toxR and vmhA from V. mimicus ; toxR from V. fluvialis ; vvhA from V. vulnificus ; and the 23S rRNA gene from P. shigelloides . The specificity of the mPCR assay was 100% for the detection of 136 strains and the limits of detection (LoD) were 12.5–50 pg/reaction. The assay exhibited higher sensitivity than cultivation methods in the detection of APW cultures of 113 diarrhea samples. In the analysis of 369 suspected Vibrio populations from estuarine water samples, the specificity of the mPCR for V. cholerae and V. parahaemolyticus was 100% for both, while the sensitivities were 100% and 96.1%, respectively. The assay can be applied to screen enrichment cultures and suspected colonies from environmental and clinical samples. Highlights: The multiplex PCR can detect five Vibrio species and Plesiomonas shigelloides. The limits of detection for the 12 genes were 12.5–50 ng/reaction. It was more sensitive than culture by screening the APW cultures of samples. It can identify suspected Vibrio populations from estuarine water samples.